2014
DOI: 10.1371/journal.pone.0101156
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Analysis of Fungal Populations in Patients with Oral Candidiasis Using Internal Transcribed Spacer Region

Abstract: Oral candidiasis is closely associated with changes in the oral fungal flora and is caused primarily by Candida albicans. Conventional methods of fungal culture are time-consuming and not always conclusive. However, molecular genetic analysis of internal transcribed spacer (ITS) regions of fungal rRNA is rapid, reproducible and simple to perform. In this study we examined the fungal flora in patients with oral candidiasis and investigated changes in the flora after antifungal treatment using length heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…However, most studies found C. albicans in the hyphal form as the cause of oral candidiasis (Coco et al, 2008;Deepa, Nair, Sivakumar, & Joseph, 2014;Samaranayake, 2009). In contrast, a previous report indicated that non-albicans Candida species were important in the pathogenesis of oral candidiasis (Ieda et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, most studies found C. albicans in the hyphal form as the cause of oral candidiasis (Coco et al, 2008;Deepa, Nair, Sivakumar, & Joseph, 2014;Samaranayake, 2009). In contrast, a previous report indicated that non-albicans Candida species were important in the pathogenesis of oral candidiasis (Ieda et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…Candida dubliniensis isolated from HIV patients with recurrent oral candidiasis showed either low susceptibility or high resistance to fluconazole (Moran et al., ). Although C. glabrata and C. dubliniensis are considered to be less susceptible to antifungal agents, a recent study showed that the detection ratio of C. glabrata and C. dubliniensis was decreased, while C. albican s persisted, after antifungal therapy using miconazole in oral candidiasis patients (Ieda et al., ). This suggests that C. glabrata and C. dubliniensis do not necessarily have low susceptibility to antifungal agents when properly selected.…”
Section: Discussionmentioning
confidence: 99%
“…Candida species, especially C. albicans is the most commonly identified fungus in the oral cavity and is considered a major pathogen of oral candidiasis1415. However, several studies indicated that non- Candida species could also be pathogenic, causing altered diversity of the oral fungal flora with an increase in resistant species against antifungal agents1617.…”
Section: Discussionmentioning
confidence: 99%
“…First, C. dubliniensis is more often recovered from oropharyngeal samples (11). Second, C. dubliniensis is isolated in a majority of cases in combination with C. albicans (65)(66)(67)(68), which could explain why opaque cells of C. albicans are more stimulatory than opaque cells of C. dubliniensis in the growth of a C. dubliniensis biofilm. This evolutionary puzzle, therefore, warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%